Functional Characterization of Cotton C-Repeat Binding Factor Genes Reveal Their Potential Role in Cold Stress Tolerance - Liu, Jiangna; Magwanga, Richard Odongo; Xu, Yanchao; Wei, Tingting; Kirungu, Joy Nyangasi; Zheng, Jie; Hou, Yuqing; Wang, Yuhong; Agong, Stephen Gaya; Okuto, Erick; Wang, Kunbo; Zhou, Zhongli; et al. (Frontiers in Plant Science, 2021)
Low temperature is a common biological abiotic stress in major cotton-growing areas. Cold stress significantly affects the growth, yield, and yield quality of cotton. Therefore, it is important to develop more robust and cold stress-tolerant cotton germplasms. In response to climate change and erratic conditions, plants have evolved various survival mechanisms, one of which induction of various stress responsive transcript factors, such as the C-repeat binding factors (CBFs), which have been found to enhance cold tolerance in various plants. In this study detailed evaluation of the cotton, CBF has been carried out. A total of 29, 28, 25, 21, 30, 26, and 15 proteins encoded by the CBF genes were identified in G. herbaceum, G. arboreum, G. thurberi, G. raimondii, G. turneri, G. longicalyx and G. australe, respectively. The phylogenetic evaluation revealed that the proteins were grouped into seven clades, with clades 1 and 6 being the largest. Moreover, the majority of the proteins encoded by the genes were predicted to be located within the nucleus, while some were distributed in other parts of the cell. Based on the transcriptome and RT-qPCR analysis, Gthu17439 (GthCBF4) was highly upregulated and was further validated through forwarding genetics. The Gthu17439 (GthCBF4) overexpressed plants showed significant tolerance to cold stress, with a higher germination rate, higher root growth, and high induction levels of stress responsive genes. The over-expressed plants exhibited a low level of oxidative damage, due to a significant reduction in H2O2 production. The results showed that the Gthu17439 (GthCBF4) could be playing a significant role in enhancing cold stress tolerance in cotton and can be further exploited in developing cotton germplasm with an improved cold-stress tolerance